ChemInform Abstract: Magnesium and Cadmium in Covalently‐Bonded Lonsdaleite Networks: Synthesis, Structure, and Bonding of AETMg2 and SrTCd2 (AE: Ca, Sr; T: Pd, Ag, Pt, Au). Issue 28 (21st June 2013) - Kersting, Marcel; Johnscher, Michael; Matar, Samir F.; Poettgen, Rainer
Abstract The title compounds are prepared by induction melting of the elements in sealed niobium ampules and characterized by powder XRD.